Predictive Value of Localized Stenosis of the Main Pancreatic Duct for Early Detection of Pancreatic Cancer - Yoshihide Kanno; Shinsuke Koshita; Takahisa Ogawa; Hiroaki Kusunose; Kaori Masu; Toshitaka Sakai; Keisuke Yonamine; Yujiro Kawakami; Yuki Fujii; Kazuaki Miyamoto; Toji Murabayashi; Fumisato Kozakai; et al. (Clinical Endoscopy, 2019)
Background/Aims: In this study, we aimed to evaluate the predictive value of localized stenosis of the main pancreatic duct (MPD) for early detection of pancreatic cancer. Methods: Among 689 patients who underwent endoscopic retrograde pancreatography from January 2008 to September 2018, 19 patients with MPD findings were enrolled. These patients showed findings for indicating suspicious pancreatic cancer at an early stage (FiCE); FiCE was defined as a single, localized stenosis in the MPD without a detectable mass (using any other imaging methods) and without other pancreatic diseases, such as definite chronic pancreatitis, intraductal papillary mucinous neoplasm, and autoimmune pancreatitis. Final diagnoses were established by examining resected specimens or through follow-up examinations after an interval of >5 years. Results: Among 19 patients with FiCE, 11 underwent surgical resection and 8 were evaluated after a >5-year observation period. The final diagnosis of the MPD stenosis was judged to be pancreatic cancer in 9 patients (47%), including 3 with intraepithelial cancer, and to be a non-neoplastic change in 10. The sensitivity, specificity, and accuracy of preoperative pancreatic juice cytology were 75%, 100%, and 88%, respectively. Conclusions: The predictive value of FiCE for pancreatic cancer prevalence was 47%. Histological confirmation with pancreatic juice cytology is necessary before surgical resection.